El tiempo y la materia en el arte contemporáneo : posibles abordajes en la formación de los profesores de artes visuales - Maddonni, Alejandra (2018)
The following text invites us to rethink the formation of the future teachers around a set of contents of the visual arts that are developed in the public space, taking into account the new configurations that the space and the contemporary time offer us. Through a couple of examples of production works, it is proposed to reflect critically around the processes of artistic production and interpretation inside and outside the classroom, to overcome certain concepts and established stereotypes and to include in the theoretical debates the new modes of perception, circulation And artistic consumption